Impact of Cigarette Price Increase on Health and Financing Outcomes in Vietnam - World Bank Group (World Bank, Washington, DC, 2019)
This paper is part of additional efforts supported by the World Bank Global Tobacco Control Program to inform the Government of Vietnam on options for tobacco taxation by providing estimates of the impact of cigarette price increase across five income groups for the period 2020-2022 under two scenarios. Vietnam is an important country for global tobacco control, and currently has about 15 million males who smoke. To support government efforts to strengthen tobacco controlpolicies, most notably through a substantial increase in the excise tax of tobacco, weconducted an extended cost-effectiveness analysis to examine the distributional impactof a 32 percent and a 62 percent increase in cigarette prices under Scenario A and Scenario B,respectively. In conclusion, we found that higher cigarette prices would particularly benefit the poorest income quintile of the population, in terms of deaths averted, life-years saved, out of pocket expenditures for treating tobacco-attributable diseases, catastrophic health expenditures, and extreme poverty averted. The additional tax burden is, however, borne mostly by the top income group in the 62 percent price increase scenario. Thus, tobacco taxes are an effective way to improve health and reduce poverty in Vietnam.